2012
DOI: 10.1097/iae.0b013e3182180114
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Spectral-Domain Optical Coherence Tomography Findings and Visual Outcome After Primary Rhegmatogenous Retinal Detachment Repair

Abstract: This study showed that not only the status of the external limiting membrane and the inner/outer segment junction but also the integrity of the intermediate line and the outer nuclear layer thickness changes may be important predictors of postoperative visual outcome after anatomically successful rhegmatogenous retinal detachment repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
87
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 21 publications
9
87
2
2
Order By: Relevance
“…In addition, we demonstrated that the integrity of backreflection on baseline SD OCT was significantly correlated with postoperative integrities of ELM and the photoreceptor layer in these patients. Previous studies have found that postoperative integrities of the ELM and photoreceptor IS/OS junction were disrupted in RRD patients with poor visual outcomes after successful surgery [23,24,25,26,27]. From these findings, the status of smudged photoreceptor layers described as ‘backreflection' on preoperative SD OCT may be a useful predictive factor for the postoperative visual outcome in macula-off RRD patients, although the precise status of the photoreceptor IS/OS junction and ELM integrities were difficult to analyze.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we demonstrated that the integrity of backreflection on baseline SD OCT was significantly correlated with postoperative integrities of ELM and the photoreceptor layer in these patients. Previous studies have found that postoperative integrities of the ELM and photoreceptor IS/OS junction were disrupted in RRD patients with poor visual outcomes after successful surgery [23,24,25,26,27]. From these findings, the status of smudged photoreceptor layers described as ‘backreflection' on preoperative SD OCT may be a useful predictive factor for the postoperative visual outcome in macula-off RRD patients, although the precise status of the photoreceptor IS/OS junction and ELM integrities were difficult to analyze.…”
Section: Discussionmentioning
confidence: 99%
“…Undulation of the separated outer retina was found to be associated with visual outcome [18,19], and the height of the subretinal fluid beneath the fovea on OCT scans has been suggested as a prognostic factor because it can disturb the interaction between the neurosensory retina and the retinal pigment epithelium [19]. In addition, the postoperative status of the photoreceptor inner segment (IS)/outer segment (OS) junction or the ellipsoid zone and external limiting membrane (ELM) have been used to predict the visual outcome in RRD patients [22,23,24,25,26,27]. …”
Section: Introductionmentioning
confidence: 99%
“…Spectral-domain optical coherence tomography provided direct visualization of in vivo retinal morphology, allowing high-resolution observation of individual layers of the macula, thereby providing greater information for structural postoperative macular changes. Recent OCT studies have reported disruptions of photoreceptor microstructures and integrity of the outer retinal bands at the fovea in cases of macula-off RRD 5,[17][18][19]32,33 and other retinal diseases (e.g., macular hole 20,34 and central serous chorioretinopathy 35 ). In the present study, SD-OCT facilitated precise measurement of retinal layer thickness and evaluation of outer retinal band integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Photoreceptor volume in cases of macula-off RRD (i.e., separation of the macula from the retinal pigment epithelium [RPE]) has been shown to be reduced compared to that in cases of macula-on RRD. 5 Persistent functional damage to the macula is observed in a proportion of eyes affected by macula-off RRD. [6][7][8][9][10][11] Factors reportedly associated with functional recovery following macula-off RRD include preoperative VA, 12 duration of macular detachment, 6,8 height of macular detachment, 13,14 and age.…”
mentioning
confidence: 99%
See 1 more Smart Citation